Petrogenesis of dark enclaves and magmatic processes in the early Paleozoic Fushui mafic complex from the Qinling Orogenic Belt, central China - Zhu, Bokang; Liao, Xiaoying; Gai, Yongsheng; Liu, Liang; Wang, Ge; Pak, Sang Wan; Yang, Wenqiang (Frontiers in Earth Science, 2025)
The dark mafic enclaves in igneous rocks provide valuable insights into the petrogenetic processes and help us understand the origin and evolution of magmas. The Early Paleozoic Fushui Complex (gabbro, hornblende gabbro and diorite) in the Qinling Orogenic Belt contains many dark enclaves, including hornblendite and dark gabbro. In this study, we systematically investigates these enclaves and the host rocks, aiming to explore their petrogenesis and relationship between the enclaves and the host rocks. On this basis, we further restored the continuous magmatic evolution of the Fushui Complex. Zircon U-Pb dating show the host rocks are crystallized at 484–492 Ma, and the hornblendite enclaves share relatively consistent crystallized ages around 500 Ma. However, some of the zircons in the hornblendite enclaves record a younger crystallized age of 475 Ma, suggesting a continuous magmatic process. The host rocks and dark gabbro enclaves exhibit arc-like trace-element signatures. In contrast, the hornblendite enclaves exhibit more variable, likely reflecting different degrees of magma mixing. While some hornblendite enclaves share similar geochemical characteristics with the host rocks, most are enriched in Th and U, depleted in high-field-strength elements and Sr, and show slightly enriched in light rare earth elements or flat REE distribution patterns. Compared to the host rocks, the hornblendites exhibit more depleted Sr-Nd isotope compositions. Trace element modeling indicates that both the enclaves and host rocks were originated from a metasomatized mantle, influenced by subducted oceanic and continental crust-derived melts. The hornblendite enclaves, characterized by orthocumulate texture, the earlier crystallization age (500 Ma), and the analysis of geochemistry and mineral chemistry, are interpreted as the early cumulates formed in a deep magma chamber, and the maximum crystallization temperature and pressure were 871°C and 13.7 kbar. The dark gabbro enclaves are characterized by fine-grained textures, field occurrence indicative of late-stage crystallization, and geochemical similarities with the host rock. These features suggest that they are the product of the rapid crystallization of the host magma at the edge of the magma chamber, then entrained by the rising magma. Their crystallization temperature and pressure are 852°C and 11.9 kbar. Integrating geochronological, geochemical, mineralogical data with previous studies, we identify three magmatic intrusion events and a subsequent greenschist-to amphibolite-facies metamorphic overprint event within the Fushui Complex. This study represents the first detailed investigation of dark enclaves in the Fushui Complex and provide new insight into their petrogenesis and the magmatic evolution.